2001
DOI: 10.1074/jbc.m011564200
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroid Hydroxylase CYP7B

Abstract: The major adrenal steroid dehydroepiandrosterone (DHEA) enhances memory and immune function but has no known dedicated receptor; local metabolism may govern its activity. We described a cytochrome P450 expressed in brain and other tissues, CYP7B, that catalyzes the 7␣-hydroxylation of oxysterols and 3␤-hydroxysteroids including DHEA. We report here that CYP7B mRNA and 7␣-hydroxylation activity are widespread in rat tissues. However, steroids related to DHEA are reported to be modified at positions other than 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 62 publications
2
40
0
Order By: Relevance
“…We have shown previously that the prostates, brains and pituitaries of the CYP7B1 Ϫ/Ϫ mice have lost the capacity to metabolize 3␤Adiol to triols (12). We found that the uteri and mammary glands of CYP7B1 Ϫ/Ϫ female mice have characteristics of tissues chronically exposed to estrogen.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…We have shown previously that the prostates, brains and pituitaries of the CYP7B1 Ϫ/Ϫ mice have lost the capacity to metabolize 3␤Adiol to triols (12). We found that the uteri and mammary glands of CYP7B1 Ϫ/Ϫ female mice have characteristics of tissues chronically exposed to estrogen.…”
Section: Discussionmentioning
confidence: 61%
“…CYP7B1 Ϫ/Ϫ mice, on a C57BL͞6J background, were provided by Richard Lathe (Pieta Research) (12). C57BL͞6J WT mice were from our colony, maintained in Huddinge University Hospital Animal Facility.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ER␤ Ϫ/Ϫ mice from our colony were used (13). ER␣ Ϫ/Ϫ mice were purchased from Taconic, and CYP7B1 Ϫ/Ϫ mice were provided by Richard Lathe (Centre for Genome Research and Centre for Neuroscience, University of Edinburgh, Edinburgh, U.K.) (14) and were bred in our laboratory. These animals were housed in Huddinge University Hospital Animal Facility in a controlled environment on a 12-h light͞12-h dark illumination schedule and fed a standard pellet diet with water provided ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…The human mRNA is present in many organs, with the highest levels detected in kidney and brain (6). The mRNA is also widely distributed among different rat tissues (7). Expression is restricted to the liver, lung, kidney, brain, and reproductive tract in the mouse, with the amount of mRNA being highest in liver and lung.…”
Section: Cyp7b1 Gene Mrna and Enzymementioning
confidence: 99%